Subthreshold Swing of 59 mV decade−1 in Nanoscale Flexible Ultralow‐Voltage Organic Transistors. (5th January 2022) - Geiger, Michael; Lingstädt, Robin; Wollandt, Tobias; Deuschle, Julia; Zschieschang, Ute; Letzkus, Florian; Burghartz, Joachim N.; van Aken, Peter A.; Weitz, R. Thomas; Klauk, Hagen
Abstract: Organic thin‐film transistors (TFTs) that provide subthreshold swings near the theoretical limit together with large on/off current ratios at very low operating voltages require high‐capacitance gate dielectrics with a vanishingly small defect density. A promising approach to the fabrication of such dielectrics at temperatures sufficiently low to allow TFT fabrication on polymeric substrates are hybrid dielectrics consisting of a thin metal oxide layer in combination with a molecular self‐assembled monolayer (SAM). Here, the electrical and surface properties of titanium oxide produced by the plasma‐assisted oxidation of the surface of vacuum‐deposited titanium gate electrodes and its use as the first component of a hybrid TiOx /SAM gate dielectric in flexible organic TFTs are investigated. These transistors have a gate‐dielectric capacitance of about 1 µF cm −2, a subthreshold swing of 59 mV decade −1 (within measurement error of the physical limit at room temperature) for a wide range of channel lengths as small as 0.7 µm, and an on/off current ratio of 10 7 for a gate‐source‐voltage range of 1 V. Abstract : Ultrathin plasma‐grown titanium oxide gate dielectrics for flexible, ultralow‐voltage organic transistors and circuits are developed. The transistors have a subthreshold swing near the physical limit of 59 mV decade −1 and a contact resistance as small as 12 Ω cm. Inverters with a small‐signal gain of 1900 at a supply voltage of 1 V are also reported.